Pengaruh Lama Perendaman Zat Pengatur Tumbuh Terhadap Pertumbuhan Macam Klon Tanaman Tebu - Agung Pranoto; Eka Adi Supriyanto (Prosiding SENTANI: Seminar Nasional Pertanian Indonesia, 2025)
Sugarcane (Saccharum officinarum L.) is a strategic commodity for fulfilling national sugar demands. One effort to improve sugarcane productivity is through the use of superior seedlings treated with plant growth regulators (PGR). This study aimed to determine the effect of soaking duration using Rootone-F PGR on the growth of several sugarcane clones. The research was conducted at KBTPH Kandeman, Batang Regency, Central Java, from January to April 2025, using a Randomized Complete Block Design (RCBD) with two factors: soaking duration (0, 10, 20, and 30 hours) and three clones (Bululawang, Kidang Kencana, PS 864). The results showed that soaking for 20 hours resulted in the highest number of tillers (10.53) and plant fresh weight (1829.87 grams). Clone treatment indicated that Kidang Kencana clone had the best performance in terms of sprouting time, plant height, stem diameter, and number of tillers. The PS 864 clone produced the highest plant fresh weight. The interaction between soaking duration and clone type did not significantly affect any of the observed variables. This study concludes that soaking sugarcane clones in Rootone-F for 20 hours is effective in enhancing sugarcane growth, particularly in the Kidang Kencana and PS 864 clones.